2016
DOI: 10.4236/ajps.2016.72026
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to Comprehend MYMIV-Susceptibility of Blackgram Cv. T9 Possessing Allele of <i>CYR1</i>, the Cognate R-Gene

Abstract: Blackgram, an important legume crop, faces the constraint of Mungbean yellow mosaic India virus (MYMIV)-stress resulting in severe crop penalty. MYMIV-resistant plants exhibit incompatible response via a cognate CYR1 gene-mediated interaction with virus effector molecule. In this study, we searched for the susceptible allele of the "R" gene in Cv. T9. Southern hybridization study confirmed presence of an allele in Cv. T9. However, transcripts of the CYR1 could not be detected either by RT-PCR or by Northern hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Hosts response to stresses relies on the timely recognition of the intruder there by integrating external cues into own cellular and physiological machinery. It was confirmed earlier that the MYMIV-susceptible T9 carried a defunct allele of the resistant gene resulted in a defective immune system 10 . Our previous study, which involved proteomic and EST analyses 5,12 showed significantly high expression of pathogen responsive genes in the resistant host that showed delayed-expression in the susceptible host.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Hosts response to stresses relies on the timely recognition of the intruder there by integrating external cues into own cellular and physiological machinery. It was confirmed earlier that the MYMIV-susceptible T9 carried a defunct allele of the resistant gene resulted in a defective immune system 10 . Our previous study, which involved proteomic and EST analyses 5,12 showed significantly high expression of pathogen responsive genes in the resistant host that showed delayed-expression in the susceptible host.…”
Section: Discussionmentioning
confidence: 58%
“…Such interactions are governed by an array of genes activated over time and inducing signal transduction cascades that decide the fate of the host. However, presence of a defunct allele of the R-gene resulted in a compatible interaction influencing pathogen colonization 10 . Seven natural mutants derived from V .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the detrimental impact of MYMIV infection, characterization of the host's resistance is imperative to identify regulatory genes and to develop new cultivars with durable resistance. In V. mungo, resistance to MYMIV has previously been reported to be governed by a resistance (R) gene, CYR1 encoding NBS-LRR protein (Maiti et al, 2012); in contrast, a defunct version of the same R-gene resulted in susceptibility, which enables pathogen colonization (Patel et al, 2016). A suppression subtractive hybridization and next-generation sequencing (RNA-seq) approach identified the genes involved in MYMIV resistance to unravel the complex molecular interaction during compatible and incompatible interactions (Kundu et al, 2015;Kundu et al, 2019).…”
Section: Yellow Mosaic Disease Caused By the Mungbean Yellow Mosaicmentioning
confidence: 99%
“…To identify the ortholog of the black gram CYR-1 gene (Patel et al, 2016) in soybean, the complete sequence of the gene was retrieved from the Phytozome database (https://phytozomenext.jgi.doe.gov/), and BLASTP search engine was used to find the most similar sequences in the soybean genome. The most identical sequences of the predicted genes in soybeans were picked, which were further confirmed by wet lab experiments.…”
Section: Confirmation Of Cyr-1 Ortholog In Soybeanmentioning
confidence: 99%
“…The CYR-1 gene was also found completely linked with MYMIV resistance in urdbean and mungbean (Maiti et al, 2011). In 2016, it was reported that the recessive form (cyr-1) of the CYR-1 gene is a susceptibility factor for YMD in black gram (Patel et al, 2016). In urdbean, RGA-1, CEDG180, ISSR811, and YMV-1 were found to be closely linked with MYMIV resistance (Basak et al, 2005;Souframanien and Gopalakrishna, 2006;Gupta et al, 2013).…”
Section: Introductionmentioning
confidence: 97%